Researching and Writing a Dissertation: An Essential Guide for Business Students - Colin M. Fisher (England Pearson, 2010)
This textbook contains sections on how to choose a topic and design the project, how to write a critical literature review, concepts, conceptual frameworks and theories, collecting and analysing research material, interpreting the research material and, finally, framing arguments and writing the dissertation.
Keywords: Research; Research methods; Textbooks; (BIN3039-N) Dissertation